(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
Pesticidal effects of different botanicals (like neem, Azadirachta indica; Biskataly, Polygonum hydropiper Linn. karanja, Pongamia pinnata, arjun (Terminalia arjuna ) and tobacco, Nicotina tabacum ) and wood ash were studied for the management of Angoumois grain moth, Sitotroga cerealella (Olivier) in stored rice grain at the Department of Entomology, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. For the studies, de-infested rice variety BR-11 was collected from farm store house. The treatments of the studies were: Neem leaf powder @ 10gm / kg of rice grains were mixed with seeds (T1); Biskatali leaf powder @ 10gm/kg of rice grains were mixed with seeds (T2); Karanja leaf powder @ 10gm / kg of rice grains were mixed with seeds (T3); Arjun leaf powder t @ 10gm / kg of rice grains were mixed with seeds (T4); Tobacco leaf powder @ 10gm / kg of rice grains were mixed with seeds (T5); Wood ash @ 10gm / kg of rice grains were mixed with seeds (T6) and Control (T7) and experiment was laid out in a Completely Randomized Design (CRD) with four replications. In all generation (1st, 2nd and 3rd generation), the results showed that different botanicals and wood ash had pesticidal effect against angoumois grain moth. Among them tobacco leaf powder showed the highest toxic effect in case of the percent of mortality (100%), percent of adult emerged (0.00%), adult longevity (0.00) and repellency effect (75%) which closely followed by neem leaf powder (T1), whereas biskataly and karanja leaves powder showed lowest and the no repellency rate (0.00) was recorded in T3 and T6 treatment. Bangladesh J. Sci. Ind. Res. 52(1), 67-72, 2017